Successful Endovascular Treatment of Acute Thromboembolic Upper Limb Ischemia in a Patient with Atrial Fibrillation - Giusca, Sorin; Schueler, Melanie; Willersinn, Eckhard; Korosoglou, Grigorios (International Journal of Angiology, 2019)
Acute limb ischemia represents a medical emergency that requires prompt diagnosis and treatment to preserve the viability of the affected tissue. The majority of the ischemic events are thrombotic in nature, especially in patients with atrial fibrillation. To date, surgical thrombectomy is usually used for the treatment of acute thromboembolic upper limb ischemia. Herein, we present a case of an 88-year-old patient who presented with right upper limb pain, pulselessness, and paresthesia. Duplex sonography revealed thrombotic occlusion and the absence of flow in both the ulnar and radial arteries. Electrocardiogram exhibited atrial fibrillation with a heart rate of 88 bpm. Antegrade puncture of the brachial artery was performed, and digital subtraction angiography confirmed fresh occlusion of the ulnar and radial arteries with some residual flow in the accessory brachial artery. Thrombus aspiration using a 6-Fr Eliminate aspiration catheter (Terumo Interventional Systems, Eschborn, Germany) was repeatedly performed, resulting in thrombolysis in myocardial infarction (TIMI) III antegrade flow to the right hand, promptly filling of the palmar arch and retrograde filling of the ulnar artery. Pain and paresthesia immediately resolved without need for further pharmacological interventions. The patient was discharged without functional deficits of his right hand, and duplex sonography after 4 weeks and 6 months revealed triphasic flow of the brachial and radial arteries and retrograde flow of the ulnar artery.
Keywords: thrombus aspiration; limb ischemia; acute occlusion; duplex sonography; upper limb; radial and ulnar arteries